The Effect Of Service Quality And Product Quality On Tart Cake Customer Satisfaction At Shop Rizky - Herlian, Herlian; Malik, Ernawati; Hasni, Hasni (International Journal of Management Progress, 2022)
The development of the economy as a whole and accompanied by the development of technology and science creates a very sharp competition. To be able to gain an advantage in terms of competition, every company must be able to meet customer satisfaction. The purpose of this stydy was to determine the effect of service quality and product quality on consumer satisfaction. The sample in this study was as many as 30 rwspondent taken from 10% of the population. The analytical tool used in this research is multiple linear regression analysis. The result showed that service quality and product quality were able to influence consumer satisfaction either partially or simultaneously. These results indicate that the better the service quality and product quality, the more customer satisfaction will increas